Effectiveness of Surgical hand Washing with Chlorhexidine, Providone iodine and Alcohol on Reducing the Microorganisms on the Hands: A Systematic Review - Haris Widodo; Tiffany Gita Sesaria; M Ruli Maulana; Nyein Moh Moh Myint (Jurnal Ners, 2019)
Background: Postoperative infection is one of the causes of mortality and the hands of the surgical team are the most common cause. According to the The Center for Disease Control and Prevention (CDC), proper hand washing can reduce the occurrence of nosocomial infections by up to 30%. The aim of this study is to determine the effectiveness of surgical hand washing using chlorhexidine, providone iodine and alcohol in reducing the microorganisms on the hand.Method: The data was collected from the following electronic databases: Science Direct, Springer link, Scopus and ProQuest. The search obtained 11 articles in accordance with the inclusion criteria and we obtained the literature in full text form.Result: The results of the study found three articles that mentioned hand washing with an alcohol hand rub as being more effective than iodine and chlorhexidine providone. There was one article described that both alcohol hand rub and chlorhexidine are more effective than iodine providone, Another article mentioned that chlorhexidine, providone iodine and alcohol hand rub were equally effective at reducing microorganisms contaminating the hand.Conclusion: The conclusion of the study is that surgical hand washing using chlorhexidine, providone iodine and alcohol are all effective at reducing microorganisms.